Economic instruments for the internalization of external costs of road transport - Preisner, Leszek; Trela, Mariusz (Economic and Environmental Studies, 2020)
In this article, the functioning of economic instruments related to the exploitation of road transport vehicles is elaborated. A critical overview of characteristics of different instruments as well as the usefulness of these instruments from the point of view of opportunities for application to a system of internalization of external costs related to the exploitation of road transport vehicles is provided in the context of advantages and disadvantages of the instruments.